Efektivitas Pembelajaran Fikih Dalam Meningkatkan Kualitas Salat Siswa - Ernawati, Yulia Ayu, Khairul Hafizin (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2025)
This study aims to examine the impact of fiqh learning on improving the quality of students' prayer worship at MTs NW 02 Rensing. It focuses on evaluating the effectiveness of fiqh instruction in enhancing students’ understanding, both conceptually and practically, in performing prayers. A quantitative approach was used with data collected through observation, Likert-scale questionnaires pretests and posttests, and interviews to support the data. The study involved 34 seventh-grade students and was conducted from June 12 to June 20, 2025, during regular fiqh lessons. SPSS software was applied to conduct the data analysis. The homogeneity test showed a significance value of 0.196, indicating homogeneous variance among the data (p > 0.05). Furthermore, statistical analysis using the paired sample t-test demonstrated a significance value equal to 0.000. indicating a statistically significant difference between pretest and posttest scores. These results suggest that fiqh learning significantly contributes to improving students' cognitive understanding and the proper practice of prayer. Structured and systematic learning is proven effective in supporting the development of both spiritual and academic aspects of students.